2003
DOI: 10.1074/jbc.m212585200
|View full text |Cite
|
Sign up to set email alerts
|

The Auxin-induced Maize Gene ZmSAUR2 Encodes a Short-lived Nuclear Protein Expressed in Elongating Tissues

Abstract: By differential screening of a cDNA library from auxin-induced maize coleoptiles we have isolated and characterized a SAUR gene, designated ZmSAUR2, belonging to a not yet characterized subtype of the SAUR family. ZmSAUR2 encodes a 15.3-kDa protein and is specifically induced by auxin in elongating coleoptile tissue but not in primary leaves or in roots. The transcript level rapidly increased within minutes and preceded auxin-stimulated elongation of coleoptile segments. Cycloheximide also induced ZmSAUR2 tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 57 publications
3
75
1
5
Order By: Relevance
“…These data suggest that SAUR36 may inhibit cell enlargement. Early studies have also shown that some SAUR proteins play a role in auxin-modulated cell elongation (Hagen and Guilfoyle, 2002;Knauss et al, 2003;Hagen et al, 2010).…”
Section: Saur36 May Also Be Involved In Leaf Cell Expansionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggest that SAUR36 may inhibit cell enlargement. Early studies have also shown that some SAUR proteins play a role in auxin-modulated cell elongation (Hagen and Guilfoyle, 2002;Knauss et al, 2003;Hagen et al, 2010).…”
Section: Saur36 May Also Be Involved In Leaf Cell Expansionmentioning
confidence: 99%
“…Like most SAUR genes in Arabidopsis (Knauss et al, 2003), the SAUR36 gene consists of only one exon (Fig. 3A) that encodes a protein with 162 amino acid residues.…”
Section: Saur36 Is Knocked Out In Two T-dna Insertion Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several GH3-like proteins covalently modify IAA, jasmonic acid, or salicylic acid, indicating that they play a global role in various hormone signaling pathways. The function of the SAUR-like genes is still unknown, but it has been suggested that they may encode short-lived nuclear proteins involved in auxin signaling by interacting with calmodulin (Yang and Poovaiah, 2000;Knauss et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are unique to plants and contain no obvious motifs suggestive of a biochemical function. Several SAUR proteins are highly unstable and appear to be subject to ubiquitin-mediated proteolysis (Knauss et al, 2003;Chae et al, 2012;Spartz et al, 2012;Li et al, 2015). However, the addition of an epitope or GFP tag can dramatically stabilize SAUR proteins.…”
mentioning
confidence: 99%